Arduino-based Gamification Tool for Multipurpose Usage in Teaching and Learning at Rural Schools. - Teng, Jun Fei (Universiti Malaysia Sarawak (UNIMAS), 2019)
The purpose of the project is to develop an Arduino-based gamification tool for multipurpose usage in teaching and learning at rural schools. In fact, rural schools that do not receive fair share of education funding directly lead to lack of basic infrastructure, no clean water supply and no 24-hour electricity supply. Thus, student in rural school eventually do not have chances to access to latest technologies to aid in learning. With the problem statement, the objective for the project is to develop a gamification prototype system using Arduino to learn physic STEM topics, develop an interactive interface to facilitate student’s learning in the topics and also create a low energy mini-projector/OHP as a solution to electricity deficient areas. Gamification through education is one of the great innovative technique that used to improve quality of education. Gamification is a way uses game thinking and game mechanic in a non-game context to engage user’s involvement. Gamification in education will motivate student in learning process and improve classroom interaction and engagement. This gamified prototype is developed using Arduino which acts as mini projector and also an overhead projector. Hence, student in rural schools able to learn STEM physic subject in Light reflection and refr interactive way. The prototype is tested at semi rural schools Sarawak and the feedback collected from the teachers and students is good and met expectations.